EXPLORE THE IMPACT OF THE COVID-19 PANDEMIC ON EXCLUSIVE BREASTFEEDING - Nurul Anjarwati; Veny Erlisa Irawan (Jurnal Kesehatan Mesencephalon, 2022)
Impact of COVID-19 pandemic on health occurred in all age groups including pregnant women, mothers giving birth, and newborns. Breastfeeding during a pandemic requires special attention because of the short-term and long-term health implications. The purpose of this study was to explore the impact of the COVID-19 pandemic on the success of exclusive breastfeeding. The research design is qualitative with in-depth interview data collection methods on 7 participants. The sample was selected according to the inclusion criteria, namely mothers who gave birth during a pandemic and when data were collected on children aged 6-12 months in the working area of the Kepanjen Health Center, Kab. Poor. Researchers as the main instrument in the study and interview guides as a reference for questions. The results of the interviews will be written in the form of transcripts and then analyzed using thematic analysis methods to obtain research themes. From the results of data analysis obtained 3 research themes. The first theme is the Practice of Early Initiation of Breastfeeding (IMD) during a pandemic, the second is the problems faced after childbirth, and the third is the practice of breastfeeding in exclusive breastfeeding during a pandemic. These results indicate that mothers need to get education and support related to breastfeeding starting from pregnancy to the success of exclusive breastfeeding. Health workers can facilitate the practice of IMD, assist mothers in solving breastfeeding problems and provide education regarding breastfeeding self-efficacy for mothers. Keywords: Nursing, exclusive breastfeeding, Covid-19 pandemic, qualitative